PENEGAKAN YURISDIKSI TERITORIAL NEGARA KESATUAN REPUBLIK INDONESIA DALAM PENCAPAIAN ASEAN PHYSICAL CONNECTIVITY - Valdemar, Renfred; Sukihana, Ida Ayu (Kertha Negara : Journal Ilmu Hukum, 2014)
For the purpose of accelerating integration among ASEAN member countries in ASEAN Community, it has been agreed on “Master Plan on ASEAN Connectivity” in order to create connectedness of ASEAN region. There are three important elements for the implementation the program, one of which is the construction of facilities and infrastructure namely ASEAN Physical Connectivity. This development will have a major impact for the territory of Indonesia as a country that has a strategic area for the traffic ASEAN regional trade. It reminds about enforcement the territorial jurisdiction of Indonesia (Republic of Indonesia) as an absolute value for the Indonesian Nation. This paper will explain the consequences and remidies that can be done to uphold the sovereignty of the territorial jurisdiction of Indonesia.
Keywords: Enforcement, Territorial Jurisdiction of the Republic of Indonesia, ASEAN Physical Connectivity